The Strategic Development for Halal Hotel: A Case Study of Krabi Province - Tantasuntisakul, Warangkana; Wongkit, Methawee (Ratchaphruek Journal, 2019)
This research was aimed at exploring the factors that are involved with developing the strategies for creating the Halal Hotel. Qualitative research methods and in-depth interviews with Semi-Structured Interview Questions were employed to collect the data. The participants of this study were the executive staff of a Halal Hotel in Krabi Province, which is registered as a member of the Krabi Halal and Muslim Friendly (KHMF). Content analysis was used to examine the data. The results revealed that Muslim travelers tend to travel in large groups with family members in comparison to other tourists. Furthermore, the hotel location appears to be the most important factor when travelers make decisions of where to stay, followed by the hotel staff, the room type, and the room facilities. In addition, the review score from the hotel’s prior guests on the Online Travel Agent (OTA) system and the hotel’s visibility on the OTA system can increase the competitive advantages of the hotel. Furthermore, being the Halal Hotel with a quality assurance certification from one of the more well-known Halal institutions is another strategy for standing out from the competition. To sum up, there are four strategies which should be emphasized in terms of developing Halal hotels namely; Product Strategy, Place Strategy, Promotion Strategy, and People Strategy.